1991
DOI: 10.1073/pnas.88.22.10352
|View full text |Cite
|
Sign up to set email alerts
|

Expanded distribution of mRNA for nerve growth factor, brain-derived neurotrophic factor, and neurotrophin 3 in the rat brain after colchicine treatment.

Abstract: The effect of intracerebroventricular iqjection of the mitosis inhibitor colchicine on expression of mRNA for nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and neurotrophin 3 was studied in the rat brain with in situ hybridization. Colchicine up-regulates mRNA for NGF and BDNF in many of the neuronal systems normally expressing these factors. In addition, after colchicine treatment NGF and BDNF mRNAs were localized in several brain areas where they normally cannot be detected. Thus, NGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 48 publications
(54 reference statements)
5
54
0
Order By: Relevance
“…Several studies reported that mhtt decreased the expression of an astroglial glutamate transporter. The consequence of lower astrocytic glutamate uptake might accelerate excitotoxicity and thus contribute to the neuronal damage in HD [48][49][50][51][52]. In the present study, we demonstrated a reduction of BDNF transcription in astrocytes by mutant htt552, suggesting a novel aspect of an astrocytic defect that might cause neuronal dysfunctions in HD.…”
Section: Discussionsupporting
confidence: 49%
“…Several studies reported that mhtt decreased the expression of an astroglial glutamate transporter. The consequence of lower astrocytic glutamate uptake might accelerate excitotoxicity and thus contribute to the neuronal damage in HD [48][49][50][51][52]. In the present study, we demonstrated a reduction of BDNF transcription in astrocytes by mutant htt552, suggesting a novel aspect of an astrocytic defect that might cause neuronal dysfunctions in HD.…”
Section: Discussionsupporting
confidence: 49%
“…The NGF contents in olfactory bulb of TSS-treated mice were immediately increased at 1 and 2 weeks, but the value returned to normal level within 3 weeks. It has been reported that activated in vivo brain astrocytes may synthesize and secrete NGF-like molecules, when the brain is damaged (25,26). Thus it has been suggested that TSS may exert its action by repairing a neurons injured by zinc sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…Because the bulk of mRNA is confined to the cell body and not to the processes for both GAD (Wuenschell et al 1986) and peptides, this method does not require pretreatment with axonal flow-disrupting drugs such as colchicine (Dahlström, 1971), by which drug-induced phenotypic expression in normally nonexpressing neurons was recently reported (Ceccatelli et al 1991;Kiyama and Emson 1991). However, the co-expression of mRNA does not necessarily indicate co-expression at the protein level.…”
Section: Discussionmentioning
confidence: 99%